Kiprah K.H. Entol Ahmad Sutisna dalam Bidang Politik di Pandeglang Tahun 1945-1982 - maesaroh maesaroh; hs suhaedi; siti fauziyah (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
The development of the Masyumi Party in Pandeglang began since Mathlaul Anwar expressed his support and joined the Masyumi Party in 1945. At that time, KH. Entol Ahmad Sutisna, who was chairman of Mathlaul Anwar, joined the Masyumi Party. In 1952 he became chairman of the Masegumi Party of Pandeglang and in 1955 he was elected to be the chairman of the DPRD Pandeglang, a representative from the Masyumi Party. KH. Entol Ahmad Sutisna is a charismatic figure who has an important contribution to the politics of the government of Pandeglang. he became the chairman of the Pandeglang DPRD which made political and economic policies. In political policy he made the Masyumi figure occupy an important position in the Government of Pandeglang, including: H. Suhaebi as the Regent of Pandegalang, KH. Maani Rusydi as the representative of the Pandeglang DPRD, Hj. Aisyah as a member of the Pandeglang DPRD, and KH. Abu Bakar Uwes as secretary of the Pandenglang DPRD, while in his economic policy he built the Pandeglang market.